Excavations at Nimrud 1949-1950 - Mallоwan, M. E. L.
Introduction — Nimrud. Historical importance. Topography — Sequence of the 1949 and 1950 excavations. Importance of the evidence obtained therefrom — The Governor's palace. Period of occupation. Discovery of the archives — History and date of the building — Historical significance of the archives — The 1950 building. Soundings in the city of Shalmaneser I — Soundings in the S. E. Palace — The N. W. Palace of Assur-nasir-pal II — Description of the plates.